Effect of Oral Herbal Medicament on Scalp Seborrhea and Gastrointestinal Symptoms in a Male Patient: A Case Report - Majid EMTIAZY; Elham ZAREIE; Laila SHIRBEIGI; Omid SADEGHPOUR; Parvin MANSOURI (Tehran University of Medical Sciences, 2018)
A 32-yr-old man with a 10-yr history of scalp seborrhea referred to Skin and Stem Cell Research Center, Tehran, Iran, in 2015. He suffered from scalp seborrhea. Concurrent gastrointestinal symptoms and the changes in the clinical symptoms after consumption of the polyherbal traditional drug called Triphala are discussed. The scalp sebum was measured with a Sebumeter SM815. Gastrointestinal symptoms were followed using a valid questionnaire. After two months of treatment, scalp sebum secretion had decreased substantially. The patient also experienced remarkable improvement in gastrointestinal symptoms. Considering the positive effect of this known and safe polyherbal drug on skin sebum, it is an appropriate option for detailed large-scale clinical trials.